KARAKTER GURU ISLAM DAN BARAT (Analisis Komparatif Pemikiran Imam az-Zarnuji Dan John Dewey) - Dariyanto; Ibnu Soleh, Muhammad; Amaliya Majid, Fitri; Dariyanto (LPPM STAI Muhammadiyah Probolinggo, 2022)
This research aims to conduct a comparative analysis of the character of teachers in Islam and the West through the thoughts of Imam az-Zarnuji and John Dewey. Imam az-Zarnuji was an Islamic scholar and educator who lived in the 12th century AD, while John Dewey was a Western philosopher and educator who lived in the early 20th century AD. These two figures have different views on education, but both have made significant contributions to the development of educational thought. This study adopts a descriptive-analytical approach to analyze Imam az-Zarnuji and John Dewey's views on teacher character in the context of Islamic and Western education. Through analysis of the texts by these two figures, we identify similarities and differences in their conceptions of the characteristics and role of a teacher. The research results show that Imam az-Zarnuji emphasized the importance of diversity in the characteristics of a teacher, including wisdom, patience and religious exemplification. Meanwhile, John Dewey emphasized the importance of direct experience and a scientific approach to teaching, as well as the role of the teacher as a facilitator of learning. From this analysis, it can be concluded that although there are differences in cultural context and thought, the concept of teacher character in Islam and the West has striking points of similarity, such as the importance of morality, wisdom, and dedication in teaching. However, practical approaches and learning methodologies may vary according to individual cultural and philosophical contexts. It is hoped that this study will provide deeper insight into the character of teachers in Islam and the West, as well as contribute to the development of cross-cultural and inter-religious education. In addition, this research also provides a foundation for a better understanding of the principles underlying educational practices in various global contexts